TRPM7 N-terminal region forms complexes with calcium binding proteins CaM and S100A1. Issue 12 (December 2021) - Bousova, Kristyna; Zouharova, Monika; Herman, Petr; Vetyskova, Veronika; Jiraskova, Katerina; Vondrasek, Jiri
Abstract: Transient receptor potential melastatin 7 (TRPM7) represents melastatin TRP channel with two significant functions, cation permeability and kinase activity. TRPM7 is widely expressed among tissues and is therefore involved in a variety of cellular functions representing mainly Mg 2+ homeostasis, cellular Ca 2+ flickering, and the regulation of DNA transcription by a cleaved kinase domain translocated to the nucleus. TRPM7 participates in several important biological processes in the nervous and cardiovascular systems. Together with the necessary function of the TRPM7 in these tissues and its recently analyzed overall structure, this channel requires further studies leading to the development of potential therapeutic targets. Here we present the first study investigating the N-termini of TRPM7 with binding regions for important intracellular modulators calmodulin (CaM) and calcium-binding protein S1 (S100A1) using in vitro and in silico approaches. Molecular simulations of the discovered complexes reveal their potential binding interfaces with common interaction patterns and the important role of basic residues present in the N-terminal binding region of TRPM. Graphical abstract: Image 1 Abstract : TRPM7, binding region, CaM, S100A1, calcium, fluorescence anisotropy.